A Polypyrrole Elastomer Based on Confined Polymerization in a Host Polymer Network for Highly Stretchable Temperature and Strain Sensors. Issue 19 (15th April 2018) - He, Yonglin; Gui, Qinyuan; Wang, Yuxuan; Wang, Zhen; Liao, Shenglong; Wang, Yapei
Abstract: For the purpose of stretchable electronics, broad interests have been paid to elastic conductors by which high tensile strain over 100% can be readily achieved. Here, a scalable‐processing, dyeing‐like strategy for highly stretchable polypyrrole elastomer (1450% in strain) is conceived without particular topological design. This approach effectively improves the mechanical properties of the classic insoluble polypyrrole by confined polymerization within an elastic polymer network. In terms of the easy processing, it is technically possible to prepare stretchable electronics with arbitrary shape and size for wearable electronics with low cost. The mechanism of interpenetrated networks coexisting with microphase separation is comprehensively illustrated at molecular scale. The as‐fabricated polypyrrole elastomers are utilized as temperature or strain sensors for automatic fishing and region‐distinct dual signal sensing. Further integration of multiple sensors offers immediate alarm for old people falling at home, which thereby proves its promising potential in practical applications. Abstract : Polypyrrole elastomers are prepared by a scalable‐processing, dyeing‐like strategy with a solvent‐free process. This approach effectively improves the mechanical properties of the classic insoluble polypyrrole by confined polymerization within an elastic polymer network. The as‐fabricated polypyrrole elastomers are utilized as temperature or strain sensors for region‐distinct dual‐signal sensing to alarm the falling of the elder at home.